(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Corrosion is a major challenge in all industrial sectors, prompting the scientific community to search for effective solutions that can stop or reduce corrosion attacks. Inhibitors (both synthetic and natural) have emerged as the ideal solution to this challenge. In this context, nano silica has been found to be a promising material due to its unique environmentally friendly properties and high surface area, capable of forming interconnected protective layers. In this study, nano silica was prepared from Najaf sand, Iraq, using the sol-gel technique, which allows precise control of particle size and porous structure. Tests were conducted to characterize the distinctive nature of nano silica. FTIR analysis revealed the presence of effective functional groups such as Si-O-Si. The chemical composition of the silica sample was examined. The results showed that the silica extracted from Najaf sand has high purity (up to 96%), enabling it to achieve high energy efficiency based on the strength of its bonds under hostile conditions, as measured by XRD. This outstanding performance is attributed to the nanoparticles' ability to diffuse effectively, as measured by surface morphology (SEM). The research confirmed the synergistic role of nanotechnology in enhancing the effectiveness of silica, as the ultrafine particles contributed to improving selective interactions with corrosive agents. The study concluded that nano-silica prepared from Najaf sand is a highly efficient and low-cost corrosion inhibitor, supported by the abundance of local raw materials. The study recommends the use of silicate inhibitors in the oil and infrastructure industries, with further research being conducted to exploit their effectiveness under various operating conditions, which will contribute to reducing economic losses and establishing principles of environmental sustainability.